Management Accounting Practices in Nepalese Manufacturing Companies - Ghimire, Keshab (Prāgyik Prabāha, 2023)
The general objective of this study was to explore the uses of management accounting practices in Nepalese manufacturing companies. This study adopted a descriptive survey design. The population of the study consists of all listed manufacturing companies under Nepal stock exchange. The study used simple random sampling. Four manufacturing firms were randomly selected for the study. The study therefore involved 5 manufacturing companies located in Kathmandu. The study collected primary data from the respondents. The data collected was both quantitative and qualitative. Analysis was done using Statistical Package for Social Sciences (SPSS), allowing the researcher to present the information in form of tables and figures. This study found that the creation and enhancement of awareness among firms of the importance of information for decision making practices as this is the most highly used management accounting practice amongst the Nepalese manufacturing companies. This study concludes that information for decision making practices is the most highly used management accounting practice amongst the manufacturing companies in Nepal, followed by strategic analysis, budgeting, performance evaluation, costing, size and leverage respectively.